Integrating Islamic principles to clinical mental health care: insights from al-Balkhi's approach to psychiatric disorder - Tengku Mohd Saifuddin Tengku Kamarulbahri,; Hanisah Mohd Noor,; Khairi Che Mat,; Siti Hajar Mohamad Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Islam places significant emphasis on mental health, urging Muslims to approach it holistically. Until now, this characterization serves as a starting point for discussing the definition and scope of Islamic spiritual care. This research aimed to provide a comprehensive overview of al Balkhi's contributions to Islamic psychology and their relevance to modern mental health practice. The methodology utilized in this research is a literature review that synthesized information from scientific texts, research reports, and historical accounts related to al-Balkhi's work. This review synthesizes Abu Zayd al-Balkhi's pioneering contributions to Islamic mental health principles, focusing on his seminal work Masalih al-Abdan Wa al-Anfus (Sustenance of the Body and Soul). This review highlights the enduring relevance of al-Balkhi's insights in mental health care, advocating for a holistic approach rooted in Islamic principles. His classifications of depressive states and therapeutic methods, like exposure-based treatments, still influence modern psychotherapy. Al-Balkhi's holistic view emphasizes the link between spiritual and physical well-being. Analyzing his theories alongside current knowledge aids in diagnosing consistently and guiding therapy effectively. Integrating historical perspectives can enhance culturally sensitive mental health interventions within Muslim communities, respecting diverse cultural contexts.